2011
DOI: 10.1002/anie.201104216
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Michael/Cyclization Reaction Sequence: Scaffold‐Inspired Synthesis of Spirooxindoles with Multiple Stereocenters

Abstract: A‐spiro‐ing: The title reaction of α‐isothiocyanato imides and methyleneindolinones has been realized for the first time using 1 as the catalyst. This newly developed synthetic method provides a simple, efficient, and environmentally friendly way to access, in an enantioselective manner, densely functionalized spirooxindoles having three contiguous stereogenic centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(55 citation statements)
references
References 55 publications
0
55
0
Order By: Relevance
“…Trost and co‐workers7a first reported an enantioselective palladium‐catalyzed [3+2] cycloaddition reaction of 3‐alkylideneoxindolin‐2‐ones with cyano‐substituted trimethylenemethane to construct spirocyclic oxindolic cyclopentanes. The groups of Melchiorre,7b Barbas,7ce Gong,7f Chen,7g Bencivenni,7h and Wang7i, j have developed several excellent organocatalytic methods to construct spirooxindoles by using methyleneindolinones in tandem reactions. Waldmann and co‐workers8 also developed a highly enantioselective Lewis acid catalyzed 1,3‐dipolar cycloaddition reaction for the synthesis of 3,3′‐pyrrolidinylspirooxindoles.…”
Section: Methodsmentioning
confidence: 99%
“…Trost and co‐workers7a first reported an enantioselective palladium‐catalyzed [3+2] cycloaddition reaction of 3‐alkylideneoxindolin‐2‐ones with cyano‐substituted trimethylenemethane to construct spirocyclic oxindolic cyclopentanes. The groups of Melchiorre,7b Barbas,7ce Gong,7f Chen,7g Bencivenni,7h and Wang7i, j have developed several excellent organocatalytic methods to construct spirooxindoles by using methyleneindolinones in tandem reactions. Waldmann and co‐workers8 also developed a highly enantioselective Lewis acid catalyzed 1,3‐dipolar cycloaddition reaction for the synthesis of 3,3′‐pyrrolidinylspirooxindoles.…”
Section: Methodsmentioning
confidence: 99%
“…However, resulting from the spiro structure, only a few transformations have achieved the goal. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] The challenges associated with the stereocontrolled construction of spirocyclic oxindole core arise from introducing quaternary carbon stereocenter at C-3 of oxindole, 22,23 which is highly sterically congested. As a result, the direct catalytic enantioselective synthesis of the spirocyclic oxindole structure with two quaternary carbon chiral centers 24,25 remains a daunting challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, when compound 7, which was prepared according to a literature procedure, [8] was employed in the developed annulation strategy the efficient and highly stereoselective formation of an unexpected reaction product (4 o) was observed (Scheme 5, bottom). It was found that MBH alcohols 1 i and 1 j derived from both electron-poor and electron-rich benzaldehydes, respectively, easily reacted under optimized reaction conditions.…”
mentioning
confidence: 99%
“…It was found that MBH alcohols 1 i and 1 j derived from both electron-poor and electron-rich benzaldehydes, respectively, easily reacted under optimized reaction conditions. [8,9] The single crystal X-ray analysis of 4 o and 4 h allowed us to unambiguously assign the relative and absolute configuration. Notably, products 4 i-l were formed as single E-isomers.…”
mentioning
confidence: 99%